Adaptive event-based tracking control of unmanned marine vehicle systems with DoS attack - Ye, Zehua; Zhang, Dan; Wu, Zheng-Guang (Journal of the Franklin Institute, 2021)
The tracking control problem of a network-based unmanned marine vehicle (UMV) system is investigated in this paper. The whole system consist of an UMV, a communication network and a ground-based control station. The measurement data collected by sensor is transmitted to the control station through communication network, and an adaptive event-triggering mechanism is introduced in this paper, which can greatly reduce the communication burden. Moreover, the aperiodic DoS attack is considered that occurs in the channel between the control station and the actuator, and no data can be transmitted when the attack occurs. The main goal is to design a Dynamic Output Feedback Control (DOFC) algorithm to track the given yaw velocity in presence of event-triggering mechanism and DoS attack. By constructing a specific Lyapunov function, the sufficient condition of global exponential stability of system with an expected H∞ disturbance attenuation index is given, and the controller gains can be obtained by solving some inequalities. Finally, the effectiveness of proposed control scheme is demonstrated by a simulation study on the networked UMV system.